Sovereignty's promise the state as fiduciary - Fox-Decent, Evan. (Oxford : Oxford University Press, 2011)
Arguing that the state and its people stand in a fiduciary relationship, 'Sovereignty's Promise' puts forward an account of political authority and its legal limits. In doing so it presents an argument for common law constitutionalism and a theoretical framework for understanding the requirements of the rule of law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sovereignty; Authority